Reverse engineering of e-Vendor for MBSA: client-server to web-based system / Laila Abdul Hamid - Abdul Hamid, Laila (2011)
The current e-Vendor system used by Majlis Bandaraya Shah Alam (MBSA) is implementing Client-Server as a platform. Several problems have been encountered in the current system on managing the vendor information. By developing the e-Vendor Web-based system will reduce the problems encountered. This system is developed using the Reverse Engineering process to determining and understanding how the current e-Vendor System works before developed e-Vendor Web-based System and also document the current system flow. The MBSA staff who are responsible to manage the vendor system is facing difficulties on using the system because there is a limitation of accessing the system. By developing e-Vendor Web-based system, the limitation of accessing the problem will be solved and staff can easily manage vendor information. The recommendation in the future for improvement and enhancement is to widen the scope to apply Reverse Engineering in the planning and analyzing process and having a better future.